Perancangan Visual Dalam Kampanye Edukasi Efisiensi Listrik Dengan Program Listrik Pintar Dari PT PLN Persero - Rizal, Muhammad Fathi Fadhil Fauzi; Murtono, Taufik (Jayapangus Press, 2025)
The presence of electricity has become a primary necessity in modern life; however, increasing electricity consumption poses a major challenge for national energy providers such as PT PLN (Persero). The Listrik Pintar (Smart Electricity) program, a prepaid service by PLN, is designed to help customers manage their electricity usage more efficiently. This study aims to design a social media-based educational campaign via Instagram to raise awareness among Generation Z regarding electricity efficiency through the Listrik Pintar program in Medan, one of Indonesia's major cities. Using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation), the study develops systematic and flexible visual educational media. Data was collected through interviews with PLN employees, Generation Z respondents, and social media strategists, as well as questionnaires, observation, and documentation. The WattWise campaign, employing a flat design visual style and an owl mascot, was implemented through the Instagram account @wattwise.id for one month. Evaluation results show a high validity score of 86% based on the Validator Evaluation Design, covering aspects of graphics, presentation, language, and context. The N-Gain effectiveness test yielded a score of 1.5, indicating high effectiveness in material delivery, with respondents’ understanding increasing from an average pre-test score of 60 to a post-test score of 90. In conclusion, this campaign proved to be both valid and effective in enhancing Generation Z's awareness of electricity efficiency and in supporting the Listrik Pintar program. The novelty of this research lies in the use of Instagram as a platform for electricity efficiency education, a field that has not yet been widely explored, with potential for further development in content and integration of Listrik Pintar program information.